The Physical Planning Implications of Housing Estate Development in Akure, Ondo State, Nigeria - Olajuyin, Olusola Isola (2015)
The study examined the physical planning implications of housing estate development in Akure with a view to providing information on the effects of location of public housing estates on the activity patterns of the residents.